2008
DOI: 10.1016/j.biopsych.2008.06.002
|View full text |Cite
|
Sign up to set email alerts
|

An Association Analysis of Murine Anxiety Genes in Humans Implicates Novel Candidate Genes for Anxiety Disorders

Abstract: BackgroundHuman anxiety disorders are complex diseases with largely unknown etiology. We have taken a cross-species approach to identify genes that regulate anxiety-like behavior with inbred mouse strains that differ in their innate anxiety levels as a model. We previously identified 17 genes with expression levels that correlate with anxiety behavior across the studied strains. In the present study, we tested their 13 known human homologues as candidate genes for human anxiety disorders with a genetic associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 56 publications
(73 reference statements)
0
38
0
Order By: Relevance
“…Some of the genes within these regions had coding SNPs known to be involved in anxiety-like behavior and/or conditioned fear; examples include the nuclear receptor subfamily 6, group A, member 1 gene [Nr6a1 (Heydendael et al 2013)], the phospholipase D1 gene [Pld1 (Sun et al 2013)], the cadherin 23 gene [Cdh23 (Terracciano et al 2010, but see Schwander et al 2009)], the prosaposin gene [Psap (Hovatta et al 2005;Donner et al 2008)], and the SLIT and NTRK-like family, member 5 gene [Slitrk5 (Shmelkov et al 2010)]. However, we are cautious about interpreting the functional relevance of nonsynonymous coding SNPs; we do not currently have expression QTL (eQTL) data that could be used to detect heritable regulatory polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the genes within these regions had coding SNPs known to be involved in anxiety-like behavior and/or conditioned fear; examples include the nuclear receptor subfamily 6, group A, member 1 gene [Nr6a1 (Heydendael et al 2013)], the phospholipase D1 gene [Pld1 (Sun et al 2013)], the cadherin 23 gene [Cdh23 (Terracciano et al 2010, but see Schwander et al 2009)], the prosaposin gene [Psap (Hovatta et al 2005;Donner et al 2008)], and the SLIT and NTRK-like family, member 5 gene [Slitrk5 (Shmelkov et al 2010)]. However, we are cautious about interpreting the functional relevance of nonsynonymous coding SNPs; we do not currently have expression QTL (eQTL) data that could be used to detect heritable regulatory polymorphisms.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, they tested 13 known human homologs as candidate genes for human anxiety disorders and showed that several of them are associated with human anxiety disorders as well. 59 Malki et al 60 treated mice from different inbred strains with antidepressant drugs and measured gene expression levels in the hippocampus. Gene expression analysis of strain-by-drug interactions revealed 17 differentially expressed genes.…”
Section: Circadian Rhythmsmentioning
confidence: 99%
“…Using this kind of approach, a SNP in the 3'UTR of the aminolevulinate dehydratase (ALAD) was found to be associated with social phobia. Even though this is not a true poly-miRTS study, this association is of particular interest since the authors comment on the possibility that this SNP generates an illegitimate target site for miR-211 and miR-204 -as predicted by a miRNA target prediction program- (Donner et al, 2008). In this regard, an important bottle-neck in the study of poly-miRTS is the identification of miRNA target sites itself.…”
Section: Trans-deregulation Of Mirnas and Anxiety Disordermentioning
confidence: 99%